2020
DOI: 10.1186/s12944-020-01354-z
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the risk factors for dyslipidemia and blood lipid indices: Ravansar cohort study

Abstract: Background: Lipid disorder is one of the most important risk factors for chronic diseases. Identifying the factors affecting the development of lipid disorders helps reduce chronic diseases, especially Chronic Heart Disease (CHD). The aim of this study was to model the risk factors for dyslipidemia and blood lipid indices. Methods: This study was conducted based on the data collected in the initial phase of Ravansar cohort study (2014-16). At the beginning, all the 453 available variables were examined in 33 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…Studies with the Skh mouse have shown that approximately equal levels of 18:3 FA were present in the plasma and epidermis of animals fed either omega-3 or omega-6 FA diets, suggesting that Δ 6 -desaturase activity was not inhibited by omega-3 FA. 25 There were differences, however, in the levels of 20:3 and 20:4 FA, with threefold higher levels in animals fed an omega-6 FA diet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies with the Skh mouse have shown that approximately equal levels of 18:3 FA were present in the plasma and epidermis of animals fed either omega-3 or omega-6 FA diets, suggesting that Δ 6 -desaturase activity was not inhibited by omega-3 FA. 25 There were differences, however, in the levels of 20:3 and 20:4 FA, with threefold higher levels in animals fed an omega-6 FA diet.…”
Section: Discussionmentioning
confidence: 99%
“… 2 , 4 Its prominent role in the etiopathogenesis of atherosclerosis and other symptoms connected to CVD is well known. 5 , 6 There are three distinct types of dyslipidemia: hypercholesterolemia (high cholesterol concentration), hypertriglyceridemia (high triglyceride [TG] concentration), and mixed hyperlipidemia (high cholesterol and TGs). 7 …”
Section: Introductionmentioning
confidence: 99%
“…Socioeconomic status was also determined using the wealth score index (WSI). The WSI was calculated by multiple correspondence analysis (MCA) of the subjects' economic and social variables [ 16 ]. According to WSI, the studied population was divided into four groups: low class, low-middle class, middle-high class, and high class.…”
Section: Methodsmentioning
confidence: 99%
“…To evaluate the intensity of physical activity, metabolic equivalent of task (MET) was used. Physical activity was assessed according to the 24 h physical activity and a 22- item questionnaire and was categorized as low (≤35.29 MET-hours per week), moderate (35.30–40.32 MET-hours per week), and heavy (≥40.32 MET-hours per week), respectively, based on the 25th and 75th percentile [ 16 ]. Questionnaires were validated by the PERSIAN [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…Hypertension was defined as SBP ≥ 140 mmHg and/or DBP ≥ 90 mmHg and/or those who were using antihypertensive drugs [24]. Dyslipidaemia was defined as a disorder in lipid profile and/or a history of consuming medication for lipid disorders [25]. In addition, Type 2 diabetes mellitus (T2DM) was defined as Fasting Blood Sugar (FBS) > = 126 mg/dl and/or history of using medication for T2DM treatment [26].…”
Section: Definitionsmentioning
confidence: 99%